Evidence-based Therapy in Vascular Surgery - Debus, E. Sebastian; Grundmann, Reinhart T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is an introduction to quality initiative for vascular surgery and medicine. Originally published in German, the book is written by leading experts who utilise their professional expertise and insight to help raise the level of patient safety, quality of care, and training of junior vascular physicians. This books aims to bring together the best available current treatment and information, including recent guidelines, meta-analyses, and randomised trials to help put evidence-based therapeutic recommendations into practice. Innovative therapeutic treatment options are not currently incorporated within standard procedure, and this book will help physicians include these methods and create more individualised treatment.
1. Carotid Artery Stenosis -- 2. Type B Aortic Dissection -- 3. Aneurysms of the descending and thoracoabdominal aorta -- 4. Aneurysms of the Abdominal Aorta -- 6. Renal Artery Stenosis -- 7. Intestinal Aneurysms -- 8. Chronic Intestinal Ischemia -- 9. Intermittent Claudication -- 10. Critical Limb Ischemia -- 11. Acute Limb Ischemia -- 12. Popliteal Artery Aneurysm -- 13. Access Surgery -- 14. Diabetic Foot -- 15. Varicose Veins.
Keywords: Medicine; Interventional radiology; Minimally invasive surgery; Vascular surgery; Medicine & Public Health; Vascular surgery; Minimally invasive surgery; Interventional radiology